Estimating expenditure pattern and permanent income hypothesis : evidence from Kelantan Malaysia - Ahmad Fahme Mohd Ali,; Naziatul Aziah Mohd Radzi,; Ruzanifah Kosnin,; Suchi Hassan,; Siti Salina Saidin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this paper is to investigate the consumption function among households in Kelantan Malaysia based on the Permanent Income Hypothesis (PIH). This study used secondary data obtained from annual reports, as well as from published and non-published data between 2000 and 2016. The ARDL bound testing approach to deal with cointegration was applied to estimate the long run correlation between the variables. Meanwhile, the error correction method (ECM) was used to determine any short run correlation. This study found a large disparity between the elasticity to consume from current income and the elasticity to consume from permanent income among households in Kelantan. Therefore, it can be concluded that in the case of Kelantan, the PIH is valid.